Sodium selenite as a new rodenticide - Jokić, Goran I; Vukša, Marina M; Đedović, Suzana; Šćepović, Tanja; Jaćević, Vesna; Stojnić, Bojan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Rodents are the most destructive group of small mammalian pests considering the overall damage that they cause by feeding and other activities, or as vectors of many disease agents. In practice, chemical rodenticides have been the most widespread and most effective method of control of commensal (Mus musculus, Rattus norvegicus and R. rattus) and most harmful field rodent pests (Apodemus sylvaticus, A. agrarius and Microtus arvalis).After anticoagulant and vitamin D3 rodenticides, which were introduced worldwide in the 1980s, no other chemical compound has had a comparable role as a rodenticide in practice. In the past decade, commercial baits containing 0.1% sodium selenite have also been registered in Serbia in various formulations both for controlling rodents indoors and in the field.Data on sodium selenite as a rodenticide have been scarce. The present paper surveysresearch data reported so far, analyzing and drawing conclusions regarding the validity and feasibility of sodium selenite as a method of rodent control with reference to the available ecotoxicological data.
Keywords: Sodium selenite; Rodents; Rodenticides